Evaluating effectiveness and safety toward electronic cigarette among Malaysian vapers: One-month observational study - Rahman, Azizur; Nik Mohamed, Mohamad Haniki; Jamshed, Shazia Qasim (Wolters Kluwer - Medknow Publications, 2016)
Objective: Electronic cigarette (e‑cig) is recently growing substitute for smoking. The attention and practice of e‑cig among consumers is expanded globally, and Malaysia is not an exception to this, but the paucity of local data motivates us to do the current research. Methods: A total of 220 e‑cig vapers recruited for the study and divided into two categories based on smoking status as a single user and dual user. Both users observed for 1 month period to assess smoking cessation rate, adverse effects, withdrawal symptoms, and smoking‑related diseases. Results: A month follow‑up showed still 28.44% (P ≤ 0.001) of the entire study population (62 of 218, intention to treat analysis) were abstained from tobacco smoking. However, a high number of single user shown more quit rate as compared to of dual users (72.9% [51] vs. 7.4% [11]: Odds ratio 33.43; 95% confidence interval: 0.102–3.410) and merely two persons (<1%) started e‑cig by ever smokers. The key adverse effects and withdrawal symptoms that observed in dual users were coughing, breathing problems, and craving, whereas in single users high appetite cases documented; however, no cases of any diseases reported among both users during the whole study period. Conclusion: A month follow‑up showed a good smoking cessation rate among Malaysian vapers mainly in single users, whereas less number of quitters but the high reduction in tobacco cigarette consumption observed in dual users without any harmful effects. Furthermore, extended period studies are warranted to confirm its long‑term safety and effectiveness among different Malaysian population.